Energy efficiency of heat pump continuous flow grain dryers - Bezrodny, M. K.; Vovk, V. V. (Energy and Automation, 2025)
Grain drying is an energy-intensive stage of post-harvest processing, where the use of heat pumps is one of the methods to improve energy efficiency. The paper provides concise information on drying technology, types of dryers, and their features. Particular attention is paid to recirculation schemes of the drying agent, which reduce energy consumption by reusing the heat carrier. Modern approaches to integrating heat pumps into continuous flow grain dryers systems are discussed, enabling dual functionality: dehumidifying air in the evaporator and heating it in the condenser. The article proposes a methodology for assessing the energy efficiency of grain drying in heat pump continuous flow grain dryers. The study also analyzes the influence of the non-isenthalpic drying mode in continuous flow dryers, a key feature that differentiates them from chamber systems. Recommendations for optimizing drying parameters to reduce energy consumption and improve dryer efficiency are provided. The research findings may be useful for agricultural enterprises seeking to modernize post-harvest grain processing technologies.Key words: grain dryer, energy efficiency, recirculation, heat pump, flow-through dryers, chamber dryers, grain moisture